Comment on “Chinese animation and its evolution and cultural background” - Yang, Hongguang (2024)
Commented Article: MAN, Shengchong. Chinese Animation and Its Evolution and Cultural Background. Trans/Form/Ação: Unesp Journal of Philosophy, v. 47, n. 4, e0240051, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14628.